If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(a + -7) + 14 = 3(a + -5) Reorder the terms: 5(-7 + a) + 14 = 3(a + -5) (-7 * 5 + a * 5) + 14 = 3(a + -5) (-35 + 5a) + 14 = 3(a + -5) Reorder the terms: -35 + 14 + 5a = 3(a + -5) Combine like terms: -35 + 14 = -21 -21 + 5a = 3(a + -5) Reorder the terms: -21 + 5a = 3(-5 + a) -21 + 5a = (-5 * 3 + a * 3) -21 + 5a = (-15 + 3a) Solving -21 + 5a = -15 + 3a Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-3a' to each side of the equation. -21 + 5a + -3a = -15 + 3a + -3a Combine like terms: 5a + -3a = 2a -21 + 2a = -15 + 3a + -3a Combine like terms: 3a + -3a = 0 -21 + 2a = -15 + 0 -21 + 2a = -15 Add '21' to each side of the equation. -21 + 21 + 2a = -15 + 21 Combine like terms: -21 + 21 = 0 0 + 2a = -15 + 21 2a = -15 + 21 Combine like terms: -15 + 21 = 6 2a = 6 Divide each side by '2'. a = 3 Simplifying a = 3
| 1-(8/x^2)=-4/x^4 | | 5.3y+0.39=3.02y-2.46 | | x(x+49)=14 | | 6x=5x-16 | | 10x^2+6x-16=0 | | s=gr-3gt^4 | | 4x^2+29x=-7 | | 6+1/3y=10+12x | | 2x+3y=36(x,2) | | (3x/x+1)-3+(3/2(x+1)) | | 3/5(-1/9) | | 3(8/6)+5= | | 4x^2-5xy-9y^2 | | 10x^2+6-16=0 | | n+(n+1)=-139 | | x-6+1=3 | | -20=8x-4x | | C=R+RXT,C=320,X=3 | | -6(V+2)+2V+7=8V+7 | | 5a-8(5a+7)=12-a | | C=R+RXT,C=320,X=5,T=3 | | (x-7)^2=-8 | | -5(2-4n)=5n+5 | | 2(2-3)(-4+7)= | | -6(V+2)+2V+7=8V+7= | | x^2+5*x-24 | | x-6+3=6 | | 8v^2=-3 | | 1+3(4p-5)=6p | | 0.4x-0.2(6-x)=1.5 | | -7(2-x)=0 | | 2+4(5x–7)=46 |